Analisis Sifat Mekanik Tanah Sebagai Faktor Penentu Pertumbuhan Tanaman - Waruwu, Frans Zefrindo Two; Waruwu, Iperiusma (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to analyze the influence of soil mechanical properties, such as texture, bulk density, porosity and consistency, on plant growth on various types of land. Soil samples were taken from rice fields, plantations and dry land to test their physical and chemical properties. The analysis results show that soil with a clay texture, low bulk density and high porosity tends to better support plant growth by providing optimal water retention and air space for the roots. Differences in land use also influence soil mechanical properties; Land with a higher organic matter content shows a more stable soil structure. The conclusion of this research is that soil mechanical properties play an important role in determining the quality of plant growth, so that good soil management can increase plant productivity in the long term.